2016
DOI: 10.1103/physrevb.93.144114
|View full text |Cite
|
Sign up to set email alerts
|

Floquet Weyl phases in a three-dimensional network model

Abstract: We study the topological properties of 3D Floquet bandstructures, which are defined using unitary evolution matrices rather than Hamiltonians. Previously, 2D bandstructures of this sort have been shown to exhibit anomalous topological behaviors, such as topologically-nontrivial zero-Chernnumber phases. We show that the bandstructure of a 3D network model can exhibit Weyl phases, which feature "Fermi arc" surface states like those found in Weyl semimetals. Tuning the network's coupling parameters can induce tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 57 publications
3
42
0
Order By: Relevance
“…(The topologically non-trivial phase is an "anomalous Floquet insulator", with interesting properties that have been studied in previous works.) [25][26][27][28][29][30][31] A topological edge invariant can be formulated for the network by truncating it in the y direction to form a strip N cells wide. Dirichlet boundary conditions are imposed on the upper and lower edges, so that no waves enter or leave via these edges.…”
Section: Exceptional Points and Topological Pumpingmentioning
confidence: 99%
“…(The topologically non-trivial phase is an "anomalous Floquet insulator", with interesting properties that have been studied in previous works.) [25][26][27][28][29][30][31] A topological edge invariant can be formulated for the network by truncating it in the y direction to form a strip N cells wide. Dirichlet boundary conditions are imposed on the upper and lower edges, so that no waves enter or leave via these edges.…”
Section: Exceptional Points and Topological Pumpingmentioning
confidence: 99%
“…Our work was motivated by recent progress in Floquet topological states [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83], in particular, Ref. [84] showed that incident light can shift the locations of Weyl points in WSMs.…”
mentioning
confidence: 99%
“…Intriguing consequences of applying light to gapless systems are now beginning to be explored: photoinduced anomalous Hall effect in Weyl semimetals 29 , chiral pumping in Dirac semimetals 30 , macroscopic chiral currents on surfaces of Dirac and Weyl semimetals 31 , to name a few. There have also been proposals to floquet engineer gapless semimetallic phases in various systems [32][33][34] .…”
mentioning
confidence: 99%